Abscopal effect of radiation therapy: Interplay between radiation dose and p53 status. (March 2014) - Strigari, Lidia; Mancuso, Mariateresa; Ubertini, Valentina; Soriani, Antonella; Giardullo, Paola; Benassi, Marcello; D'Alessio, Daniela; Leonardi, Simona; Soddu, Silvia; Bossi, Gianluca
Abstract Purpose: This study investigates whether the abscopal effect induced by radiation-therapy (RT) is able to sterilize non-irradiated tumour cells through bystander signals. Material and methods: Wild-type (wt)-p53 or p53-null HCT116 human colon cancer cells were xenografted into both flanks of athymic female nude mice. When tumours reached a volume of 0.2 cm3, irradiation was performed, under strict dose monitoring, with a dedicated mobile accelerator designed for intra-Operative-RT (IORT). A dose of 10 or 20 Gy (IR groups), delivered by a 10 MeV electron beam, was delivered to a tumour established in one side flank, leaving the other non-irradiated (NIR groups). A subset of mice were sacrificed early on to carry out short-term molecular analyses. Results: All directly-irradiated tumours, showed a dose-dependent delayed and reduced regrowth, independent of the p53 status. Importantly, a significant effect on tumour-growth inhibition was also demonstrated in NIR wt-p53 tumours in the 20 Gy-irradiation group, with a moderate effect also evident after 10 Gy-irradiation. In contrast, no significant difference was observed in the NIR p53-null tumours, independent of the dose delivered. Molecular analyses indicate that p53-dependent signals might be responsible for the abscopal effect in our model system, via a pro-apoptotic pathway. Conclusions: We suggest that the interplay between delivered dose and p53 status might help to sterilize out-of-field tumour cells.